The attitude and real customer's behavior using mobile banking in Bank Jatim Pare - Suseno, Rendi (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
ABSTRACT Â The presence of modern banking service products such as mobile banking should meet the requirements of a technology to be adopted. In fact the problem that arises in the use of a technology at Bank Jatim is the low utilization of the service system. This condition challenges researchers to test through technology acceptance model theory with modification of models to explain the conditions of acceptance of a new technology. The conclusion of this study found that from the model that had been compiled that the three exogenous variables were tested, only the ease of perception variables that proved to have a significant contribution to both attitudes of use and the actual behavior of use. In addition, perceived convenience variables also have a significant positive influence on customer trust. However, the results of the study found that the contribution of trust and trust variables was still low in shaping attitudes towards the use and real behavior of using mobile banking services. Another finding in this study to describe the problem of the low use of mobile banking services is the need for cash transactions by customers. Most PNS customers need cash transactions in their daily routine compared to the needs of non-cash transactions such as transfers or purchases online. This is what causes customers to use the Automated Teller Machine service as a means of taking their money and then use the transaction directly as neededÂ